Metagenomic Analysis Reveals a Changing Microbiome Associated With the Depth of Invasion of Oral Squamous Cell Carcinoma - Liu, Yuan; Li, Zhengrui; Qi, Yanxu; Wen, Xutao; Zhang, Ling (Frontiers in Microbiology, 2022)
The relationship between oral squamous cell carcinoma (OSCC) development and the microbiome has attracted increasing attention. The depth of invasion (DOI) is an important indicator of tumour progression, staging and prognosis, and the change in the oral microbiome based on the DOI is unclear. This report describes the use of metagenomic analyses to investigate the relationship between the oral microbiome and the DOI. Forty patients in different DOI categories were recruited; 10 healthy people served as the control group. Swab samples collected from the participants were subjected to metagenomic analyses, and the oral microbial communities and their functions were investigated. The abundances of Fusobacterium nucleatum, Capnocytophaga sputigena, Porphyromonas endodontalis, and Gemella haemolysans were significantly increased in the patients compared with the controls. The abundances of some bacteria exhibited a stage-related trend. The abundances of P. endodontalis, Gemella morbillorum and G. haemolysans increased with increasing DOI. In contrast, the abundances of Prevotella melaninogenica, Haemophilus parainfluenzae and Neisseria flavescens decreased with increasing DOI. Based on receiver operating characteristic (ROC) curve analysis, eight species were found to have predictive value: Rothia mucilaginosa, P. melaninogenica, H. parainfluenzae, and N. flavescens in the healthy control group and P. endodontalis, G. morbillorum, G. haemolysans and Fusobacterium periodonticum in the high DOI group. In the functional analysis, several metabolic pathways were decreased, whereas flagellar assembly and bacterial chemotaxis showed an increasing trend as the disease progressed. Biofilm formation, flagella, lipopolysaccharide (LPS) and other virulence factors exhibited staging-related changes. These pathogenic pathways and factors had a clear correlation with specific pathogens. In particular, when OSCC progressed to the late stage, microbial diversity and functional potential changed greatly.